AN ANALYSIS OF THE MONETARY TRANSMISSION MECHANISM OF PROFIT-SHARING FINANCING IN INDONESIA - Herianingrum, Sri; Fathy, Ummi Muthi`ah (Universitas Airlangga, 2016)
This research is aimed to determine the importance of profit loss sharing financing in the monetary transmission process in the Indonesian economy. The study analyzes the effective of profit loss sharing financing in channelling the monetary policy effecs to the real economy. This research used the quantitative research method and used granger causality test, impulse response functions and variance decomposition analysis, focusing on the period from January 2010 to Aprl 2015. The results showed that there granger causality in the monetary transmission process there is causality in one direction from the variable FASBIS to FLPS, FASBIS to DPK.There is a two-way causality between variables CPI to / from FLPS, deposits to / from FLPS, SBIS to / from FASBIS.Funding for the results (FLPS) responds variable shock SBIS, FASBIS, deposits and CPI based on test results IRF.In general FLPS response to all variables fluctuate at the beginning of the period (period-1 to period 8), and starts balanced in the period from the 9th or the 25th month.Funding for the results contribute to the ultimate objective of monetary policy is inflation (CPI), but the contribution of financing for the results is relatively small, because although ranked second, but the contribution is only 2.57%.